2019
DOI: 10.5194/acp-19-5051-2019
|View full text |Cite
|
Sign up to set email alerts
|

Taehwa Research Forest: a receptor site for severe domestic pollution events in Korea during 2016

Abstract: Abstract. During the May–June 2016 International Cooperative Air Quality Field Study in Korea (KORUS-AQ), light synoptic meteorological forcing facilitated Seoul metropolitan pollution outflow to reach the remote Taehwa Research Forest (TRF) site and cause regulatory exceedances of ozone on 24 days. Two of these severe pollution events are thoroughly examined. The first, occurring on 17 May 2016, tracks transboundary pollution transport exiting eastern China and the Yellow Sea, traversing the Seoul Metropolita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
3
11
0
1
Order By: Relevance
“…Cheng et al, , 2018. On average, there is a lower combustion efficiency in China than in Korea, with the ratio of CO to CO 2 changing accordingly as shown by the DC-8 measurements during KORUS-AQ (Halliday et al, 2019) and indicated by model simulations (Tang et al, 2018). Tracking CO 2 and CO from fossil fuel emissions could be combined to further constrain fossil fuel emission fluxes.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Cheng et al, , 2018. On average, there is a lower combustion efficiency in China than in Korea, with the ratio of CO to CO 2 changing accordingly as shown by the DC-8 measurements during KORUS-AQ (Halliday et al, 2019) and indicated by model simulations (Tang et al, 2018). Tracking CO 2 and CO from fossil fuel emissions could be combined to further constrain fossil fuel emission fluxes.…”
Section: Discussionmentioning
confidence: 96%
“…The intensive measurement period was from 1 May and 15 June 2016 with the deployment of a research vessel (Thompson et al, 2019) and four different aircraft: the NASA DC-8, the NASA B200, the Hanseo University King Air, and the Korean Meteorological Agency (KMA) King Air. The aircraft sampled numerous vertical profiles of trace gases, aerosols, and atmospheric physical parameters with a missed approach flying procedure over the SMA (e.g., Nault et al, 2018) and spiral patterns over the Taehwa Research Forest (TRF), downwind from the SMA (e.g., Sullivan et al, 2019). Peterson et al (2019) studied the weather patterns during KORUS-AQ and distinguished four distinct periods defined by different synoptic patterns: a dynamic meteorological phase with complex aerosol vertical profiles, a stagnation phase with weaker winds, a phase of efficient long-range transport, and a blocking pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to observations, the simulations underestimated the ClNO 2 maxima levels by ∼ 7 times in inland areas (Sherwen et al, 2017). Modeling studies have consistently suggested the significance of Cl q -initiated reactions in regional and global O 3 production and in the lifetime of VOCs in the troposphere (Knipping and Dabdub, 2003;Tanaka et al, 2000Tanaka et al, , 2003Sarwar et al, 2014;Sherwen et al, 2016;Simon et al, 2009). Sarwar et al (2014) explored the production of ClNO 2 from sea salt and biomass burning and its impact in the Northern Hemisphere by including ClNO 2 formation chemistry in the CMAQ model.…”
Section: Introductionmentioning
confidence: 99%
“…During the day, N 2 O 5 exists at low levels due to its thermal instability (Malko and Troe, 1982) and the short lifetime of NO 3 (τ NO 3 < 5 s) from photolysis and reaction with NO (Wayne et al, 1991). Particulate Cl − and chlorine-containing gas species can come from both natural sources such as sea salt and biomass burning (Blanchard, 1985;Woodcock, 1953) and anthropogenic sources such as steel making, incineration, bleaching processes, and coalfired power plants (Hov, 1985;Reff et al, 2009;Tanaka et al, 2000;Lee et al, 2018;Fu et al, 2018). The efficiency of ClNO 2 production depends on heterogeneous loss of N 2 O 5 , which is a function of the N 2 O 5 aerosol uptake coefficient (γ N 2 O 5 ), aerosol surface area, and N 2 O 5 mean molecular speed, as well as the yield of ClNO 2 (φ ClNO 2 ) (e.g., Thornton et al, 2003;Schweitzer et al, 1998;Behnke et al, 1997;Hu and Abbatt, 1997;Bertram and Thornton, 2009).…”
Section: Introductionmentioning
confidence: 99%